Hyperspectral reflectance imaging for nondestructive evaluation of root rot in Korean ginseng (Panax ginseng Meyer) - Park, Eunsoo; Kim, Yun-Soo; Faqeerzada, Mohammad Akbar; Kim, Moon S.; Baek, Insuck; Cho, Byoung-Kwan (Frontiers in Plant Science, 2023)
Panax ginseng is a widely used medicinal herb. Although its global production has increased in recent years, the yield of 4–6 years-old ginseng has decreased by 30–60% due to diseases such as root rot. Root rot is caused by Cylindrocarpon destructans, a soil-borne fungus capable of overwintering. It usually occurs when the plant is >4 years old, and the disease spreads from the tip of the tap root to the crown root, leaves, and stem. Root rot is typically diagnosed by frequently checking the ginseng plants for root rot or by evaluating soil pathogens in a farm, which is a time- and cost-intensive process. Because this disease causes huge economic losses to ginseng farmers, it is important to develop reliable and non-destructive techniques for early disease detection. In this study, we developed a non-destructive method for the early detection of root rot. For this, we used crop phenotyping and analyzed biochemical information collected using the hyperspectral imaging (HSI) technique. Soil infected with root rot was divided into sterilized and infected groups and seeded with 1-year-old ginseng plants. HSI data were collected four times during weeks 7–10 after sowing. The spectral data were analyzed and the main wavelengths were extracted using partial least squares discriminant analysis. The average model accuracy was 84% in the visible/near-infrared region (29 main wavelengths) and 95% in the short-wave infrared (19 main wavelengths). These results indicated that root rot caused a decrease in nutrient absorption, leading to a decline in photosynthetic activity and the levels of carotenoids, starch, and sucrose. Wavelengths related to phenolic compounds can also be utilized for the early prediction of root rot. The technique presented in this study can be used for the early and timely detection of root rot in ginseng in a non-destructive manner.